Planning the mirage: Lessons for planning education from Abu Dhabi (Transactions of the Association of European Schools of Planning, 2019)
Throughout the 1980s planning educators disagreed on the appropriateness of Western planning education for poor countries’ students, and on the question of whether training of students from developing countries should be based on “general principles” or “contextual material specific to poor countries” (Sanyal, 1990, p.8). Today most planning programs in North America (and in the West in general) offer courses in ‘international development’, ‘world cities’, ‘urbanization in the global South’, or closely related topics. However, as ‘the other’ becomes more mainstream in Western planning education, the belief that Western planning education is robust enough to accommodate global differences (the ‘one world’ model of planning education), becomes more entrenched. Further, an unspoken assumption goes unquestioned – that planning curricula, too, just like planning skills, can be transferred internationally. Over the last three decades or so, the advent of the age of interconnected economies and the networked society, has had a profound impact on global trends of development and urbanization. This paper argues that the question of appropriate planning curricula ought to be revisited especially from the perspective of education in developing countries. Scholars educated in the West, who are teaching in developing countries, are in a unique position to assess the utility of bringing Western planning education to less developed parts of the world. This paper is based on the authors’ observations and experiences over seven years, teaching Urban Planning at undergraduate level at a private university in Abu Dhabi. During this period the authors were involved with program design, course design, accreditation and quality assurance, mentorship, along with university service, teaching, and research. The paper evaluates the practices and circumstances of urban planning in UAE and the implications for planning education. It is argued that there is a fundamental disconnect between the profession’s ethics, and the reality of planning practice in the region. This gap has not been considered in depth in either program design or in accreditation standards. The paper concludes with recommendations for planning education in the Gulf region.
Keywords: planning education; uae; gulf; global south; one world planning